Karakteristik Sosial Ekonomi Rumah Tangga Petani dan Tingkat Kesejahteraan Rumah Tangga Petani di Kelurahan Guntung Manggis Kecamatan Landasan Ulin Kota Banjarbaru - Erma Erma; Suprijanto Suprijanto; Muhammad Husaini (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
The farmer prosperity is represented by socio-economic characteristic of the household. This means each farmer has different way of life and different response to the factor determined their welfare. The purposes of study are: (1) to assess the socio-economic characteristic of farmer household; (2) to determine the prosperity level; and (3) to analyze the correlation of socio economic characteristics and the farmer prosperity level at the study site. The socio-economic characteristics include farming experience , formal education, land acreage and status, household asset, and farmer activity in farmer group. The result pictures that the socio-economic characteristics is relatively good since the most of household heads are in the productive age, has the adequate farming experience, and has low number of dependents. The farmer's activity in the farmer group is considered high and very high. However, the formal education level low and the landholding is incapacious. Based on the prosperity criteria, the prosperity level of the farmer in study site is in Prosperity Level II. In addition, the correlation between the characteristics and the household prosperity is is strong.